(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2026)
The development of eco-friendly nanomaterials has become a central objective in modern materials science due to growing concerns about environmental sustainability and energy demand. Conventional methods for synthesizing metal–oxide nanocomposites often require toxic precursors and energy-intensive processes, whereas green synthesis provides a safer and more sustainable approach by utilizing plant-derived phytochemicals, aqueous media, and mild reaction conditions. In this study, three nanocomposites—CeO₂–ZnO, ZnO–SnO₂, and NiO–ZnO were prepared using green routes, including plant-mediated extract synthesis, sol–gel, and co-precipitation. The materials were thoroughly characterized by XRD, SEM, TEM, FTIR, UV–Vis, and BET techniques to examine their crystalline structure, morphology, functional groups, optical properties, and surface area. The nanocomposites were subsequently tested for three different applications: photocatalysis, solar cells, and supercapacitors. The results demonstrated that all composites exhibited enhanced performance compared with their single-oxide counterparts. Specifically, they achieved over 90% photocatalytic efficiency in dye degradation, improved power conversion efficiency in dye-sensitized solar cells, and high specific capacitance and cycling stability in supercapacitors. These findings highlight the potential of green-synthesized nanocomposites as multifunctional materials that combine environmental remediation with renewable energy conversion and storage. The outcomes of this work point toward the feasibility of scaling up green synthesis approaches and integrating such materials into hybrid energy and environmental systems.